The effect of parental marital status on non-suicidal self-injurious behavior among middle school students in rural western China: a multicenter cross-sectional study based on propensity score matching method - Ren, Xiaohong; Pan, Lu; Song, Yuqin; He, Ping; Wu, Dapeng; Luo, Jiaming (Frontiers in Psychiatry, 2025)
IntroductionParental marital status is a pivotal determinant of adolescent maladaptive behaviors. However, the specific correlation between parental marital status and Non-Suicidal Self-Injury (NSSI) among adolescents in western China has not been thoroughly investigated.MethodsA cross-sectional study was conducted involving 7,274 students from non-divorced families and 1,332 from divorced families. Participants were assessed using the Ottawa Self-Injury Inventory (OSI) and the Depression, Anxiety, and Stress Scale-21 Items (DASS-21). Propensity score matching (PSM) was applied to control for confounders, and logistic regression was used to analyze associations.ResultsThe prevalence of non-suicidal self-injury (NSSI) was higher in adolescents from non-divorced families (4.1%) than in those from divorced families (1.6%). However, propensity score matching analysis revealed that parental divorce was associated with a significantly increased odds of NSSI after controlling for confounders. Furthermore, depression and anxiety were identified as independent risk factors for NSSI. Mediation analysis indicated that the emotional distress (depression, anxiety, and stress) did not significantly mediate the relationship between parental divorce and NSSI. Additional significant predictors of NSSI included girls and age.DiscussionAdolescents from divorced families in western China show a higher incidence of NSSI, though this relationship is not mediated by emotional distress. These findings highlight the need for families and society to enhance attention to the psychological well-being of this vulnerable adolescent population.